Kreativitas Ujang Sitertone Dalam Membuat Kacapi Sitertone - Azis Nur Soleh (Paraguna, 2022)
Creativity is a person's ability to produce a new work that comes from himself or the development of an existing work so that it becomes a new work. Ujang Sitertone has done this creative thing by developing a Kacapi siter which is combined with Midi technology to create a Kacapi sitertone. The purpose of this research is to describe, document and introduce Ujang's Kacapi sitertone which is not known to many people. This study uses qualitative methods with data collection techniques, namely documentation, observation, and interviews. Kacapi Sitertone is an innovation of Kacapi siter that has the advantage that it can accompany various genres of songs using styles such as keyboard/organizational/electronic. The songs that can be accompanied by Kacapi are also very diverse, ranging from old songs, Sundanese Pop, Indonesian Pop, Western, Reggae to Keroncong.